The Integration of Islamic Law into Domestic Violence Prevention Strategies - Muhammadong Muhammadong (Maksimal Jurnal : Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2026)
Preventing domestic violence is a major problem in the world, including Indonesia, and it needs to be dealt with in a whole way. In this context, the incorporation of Islamic law can serve as an effective technique for the prevention of domestic violence, given the moral and ethical ideals inherent within it. This study seeks to examine the application of Islamic law integration in domestic violence prevention measures in Indonesia. The employed study methodology is qualitative, utilizing a literature review to analyze Islamic legal texts concerning familial rights and responsibilities and their practical application in everyday life. The study's findings demonstrate that Islamic law delineates explicit directives concerning the responsibilities of husbands, wives, and families in promoting equitable and peaceful relationships, while also forbidding any manifestation of violence. Moreover, ideals such as justice, compassion, and respect for personal dignity can underpin the formulation of more efficacious domestic violence prevention programs. This study underscores the significance of socialization and the implementation of Islamic law in preventive measures against domestic violence within society.